Gadamer on the Event of Art, the Other, and a Gesture Toward a Gadamerian Approach to Free Jazz - Cynthia R. Nielsen (University of Calgary, 2016)
Several prominent contemporary philosophers, including Jürgen Habermas, John Caputo, and Robert Bernasconi, have at times painted a somewhat negative picture of Gadamer as not only an uncritical traditionalist, but also as one whose philosophical project fails to appreciate difference. Against such claims, I argue that Gadamer’s reflections on art exhibit a genuine appreciation for alterity not unrelated to his hermeneutical approach to the other. Thus, by bringing Gadamer’s reflections on our experience of art into conversation with key aspects of his philosophical hermeneutics, we are able to better assess the viability of Gadamer’s contributions to contemporary discussions of difference and alterity.